2006
DOI: 10.1128/aem.00808-06
|View full text |Cite|
|
Sign up to set email alerts
|

Unlocking Streptomyces spp. for Use as Sustainable Industrial Production Platforms by Morphological Engineering

Abstract: Filamentous actinomycetes are commercially widely used as producers of natural products (in particular antibiotics) and of industrial enzymes. However, the mycelial lifestyle of actinomycetes, resulting in highly viscous broths and unfavorable pellet formation, has been a major bottleneck in their commercialization. Here we describe the successful morphological engineering of industrially important streptomycetes through controlled expression of the morphogene ssgA. This led to improved growth of many industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
119
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(127 citation statements)
references
References 25 publications
4
119
1
Order By: Relevance
“…Secretion at apical sites would imply that fragmented growth is favorable because it increases the number of hyphal tips per length unit, as opposed to when production primarily takes place inside mycelial clumps. Interestingly, production of enzymes through the twin arginine translocation (Tat) exporter occurs closely behind the hyphal tips in S. coelicolor (16,394); in line with this concept, Tat substrates are secreted more efficiently in fragmenting strains of S. coelicolor and S. lividans (313). An extensive review of the industrial implications of the correlation between growth and natural product formation is be-yond the scope of this review, so we refer the interested reader elsewhere (24,(395)(396)(397)(398).…”
Section: Correlation Between Growth and Antibiotic Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secretion at apical sites would imply that fragmented growth is favorable because it increases the number of hyphal tips per length unit, as opposed to when production primarily takes place inside mycelial clumps. Interestingly, production of enzymes through the twin arginine translocation (Tat) exporter occurs closely behind the hyphal tips in S. coelicolor (16,394); in line with this concept, Tat substrates are secreted more efficiently in fragmenting strains of S. coelicolor and S. lividans (313). An extensive review of the industrial implications of the correlation between growth and natural product formation is be-yond the scope of this review, so we refer the interested reader elsewhere (24,(395)(396)(397)(398).…”
Section: Correlation Between Growth and Antibiotic Productionmentioning
confidence: 99%
“…The connection between mycelial morphology and production is further exemplified by avermectin production by S. avermitilis, which is favored by small dense pellets (384), and by S. coelicolor, in which forced fragmentation by overexpression of the cell division activator protein SsgA abolishes actinorhodin production. However, it is dangerous to generalize, as the same strain shows a 20-to 50-fold increase in undecylprodigiosin production in a fermentor (310,313,315), and chloramphenicol production by Streptomyces venezuelae is not hampered by the extremely fragmented growth of the producing organism (385,386). It was previously suggested that antibiotics that are produced during exponential growth may benefit from fragmented growth, while those produced during the transition or stationary phases are produced much more efficiently by clumps (236).…”
Section: Correlation Between Growth and Antibiotic Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…GltS is a flavin dependent iron sulfur cluster protein [86]. It is worth noting that the reverse of these reactions, producing 2-oxoglutarate, allows the carbon from glutamate to enter the citric acid cycle and many organisms are capable of using glutamate as their sole carbon source, possibly even preferring it over glucose [84]. …”
Section: Introductionmentioning
confidence: 99%
“…SsgA was identified as a sporulation protein in S. griseus [24], and enhanced expression of SsgA affects fragmentation of mycelia in liquid-grown cultures [25,26]. SsgA is required for both solid- and liquid-culture sporulation of streptomycetes and is a key connection between these two types of cell division.…”
Section: Introductionmentioning
confidence: 99%